2008
DOI: 10.1007/s00247-008-0987-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of lung infections in children

Abstract: The advantages and limitations of MRI in lung infections in children have not been well established. This article illustrates the MRI findings in children with pneumonia caused by Mycoplasma pneumoniae, Streptococcus pneumoniae, and other pathogens. Lung parenchymal, pleural, and lymph node abnormalities are well characterized by MRI. Loculation of pleural fluid is detected in children with empyema. Contrast enhancement may be useful in the differentiation of active inflammation from noninflammatory changes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
22
0
2
Order By: Relevance
“…65 Evidence for the accuracy of MRI and interobserver agreement in interpreting pneumonia in children is agreement in the interpretation of chest radiographs is poor. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In a recent review, 10 of 12 pediatric studies showed only fair to moderate interobserver agreement. 38 Agreement is worse for reporting of an "infiltrate" in children under 5 years, 23 and it remains moderate even when using WHO standardized radiological criteria for pneumonia.…”
Section: Rapid Sequence Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…65 Evidence for the accuracy of MRI and interobserver agreement in interpreting pneumonia in children is agreement in the interpretation of chest radiographs is poor. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In a recent review, 10 of 12 pediatric studies showed only fair to moderate interobserver agreement. 38 Agreement is worse for reporting of an "infiltrate" in children under 5 years, 23 and it remains moderate even when using WHO standardized radiological criteria for pneumonia.…”
Section: Rapid Sequence Mrimentioning
confidence: 99%
“…Ultrasound has several advantages over other imaging modalities: it can be performed at POC, it is feasible and less costly than chest radiography, it is less affected by movement or crying than other imaging modalities, it can be done in sleeping children, 35 and it is free of ionizing radiation. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although ultrasound performed by non-radiologists is controversial, it has become a useful tool for physicians, emergency medicine doctors, and intensivists. 44 Lung ultrasound involves scanning a child in the anterior, lateral, and posterior areas of each hemithorax.…”
Section: Advances In Radiological Diagnosismentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) can detect loculi and differentiates between inflammatory and noninflammatory changes if contrast enhancement is used [21]. At present, the restricted availability of MRI together with logistic problems limits it use in acutely sick children.…”
Section: Imagingmentioning
confidence: 99%
“…Lodi et al. detail a 48 year old male with several lymph nodes up to 50mm [9], whilst the remaining reports detail paediatric cases with lymph nodes up to 18mm [4], [12].…”
Section: Discussionmentioning
confidence: 99%